Pengaruh Waktu Pemanasan Menggunakan Pemanas Induksi Terhadap Kekerasan dan Struktur Mikro Material S50C - Viktor Naubnome; Eri Widianto; Marno Marno (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2017)
Fabrication of inducting heating system for heating treatment in S50C materials have been done. This inducting heating system has dimensions of 350x230x200 mm, the input voltage of 12 VDC, equipped with a timer control and ampere meter as an indicator of output current. Inducting heating system testing on the material S50C was done by varying tempering process (30, 60, 90, 120 and 150 s). Hardness and microstructure test using Auto Vikers Future Tech type FV-300. The results showed that the hardness increased with increasing tempering time from 191 Hv to 572 Hv. S50C materials microstructure was transformed from ferrite and pearlite phase into martensite phase.